2014
DOI: 10.1016/j.pjnns.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of hypervolemic therapy in patients after subarachnoid haemorrhage

Abstract: This study revealed inconsistencies in the fluid orders as well as mistakes in the fluid monitoring, which illustrates the difficulties of fluid therapy and reinforces the need for strong evidence-based guidelines for hypervolemic therapy in SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Of the included studies, 18 reported the prevalence of patients with fluid balance monitored using a fluid balance chart. Of those, seven found a proportion of complete fluid balance charts of no more than 25%,33 43 45 46 48 50 54 three studies found a proportion between 26% and 50%,36 40 47 and in five studies, the proportions were reported to be between 51% and 75% 32 37 39 41 42. Only three studies reported that more than 75% of patients had a complete fluid balance chart34 35 38 (figure 2).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Of the included studies, 18 reported the prevalence of patients with fluid balance monitored using a fluid balance chart. Of those, seven found a proportion of complete fluid balance charts of no more than 25%,33 43 45 46 48 50 54 three studies found a proportion between 26% and 50%,36 40 47 and in five studies, the proportions were reported to be between 51% and 75% 32 37 39 41 42. Only three studies reported that more than 75% of patients had a complete fluid balance chart34 35 38 (figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The studies comprised 12 studies categorised as quasi-experimental,33 40–43 45–47 49–51 54 3 cohort studies32 37 44 and 8 prevalence studies (cross-sectional studies) 34–36 38 39 48 52 53. All were appraised using the JBI tools for assessing quasi-experimental and prevalence studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations